The Idea of a Three-Dimensional Conflicts Law as Constitutional Form - Joerges, Christian (RECON Online Working Paper 2010/05, 2010)
‘Constitutionalisation’ is the key concept in the search for legitimate governance in the European Union and in the international system. This paper suggests the revitalising of a discipline which is widely neglected in European law and international law scholarship. It does not, however, recommend a return to the conflict of laws (private international law) in the traditional sense. The new type of conflicts law that the paper advocates is not concerned with selecting the proper legal system in cases with connections to various jurisdictions. This conflicts law is conceptualised as a response to the increasing inter-dependence of formerly more autonomous legal orders and to the democracy failure of constitutional states which result from the external effects of their laws and legal decisions on foreign systems and on their citizens who cannot understand themselves as their authors. European law has a vocation and many means both to compensate for the democracy failures of member states and to build upon this potential in its constitutionalisation. The conflicts law approach also provides new, albeit more restrained, perspectives at international level. WTO law is used to explore and document its constitutional perspectives. The conflicts law approach is differentiated into three dimensions. With this differentiated fabric, the approach responds to transformation processes which have affected contemporary law at all levels of governance after the rise of regulatory politics and the turn to governance. In its second dimension, conflicts law seeks to constitutionalise co-operative problem-solving under the lead of administrative bodies, while its third dimensions is concerned with both the recognition and the supervision of transnational governance arrangements and para-legal regimes.
Keywords: BLOCK, Fred; Europeanisation; World Trade Organization (WTO); always socially embedded' economy; constitutionalisation; deliberative democracy; economic law; economic sociology; multilevel governance; private international law; rule of law; social embeddedness; social regulation; supranationalism

Polanyi in Brussels? Embeddedness and the Three Dimensions of European Economic Integration - Höpner, Martin; Schäfer, Armin (Max-Planck-Institut für Gesellschaftsforschung, 2010)
In a recent article, Caporaso and Tarrow have argued that the jurisprudence of the European Court of Justice (ECJ) is increasingly moving in a social policy direction that will ultimately put European politics on a “Polanyian” course. We take issue with their claim and distinguish three dimensions of European economic and social integration: market-correcting integration, market-enforcing integration, and the creation of a European area of nondiscrimination, the latter consisting of two subdimensions, namely nondiscrimination on the basis of characteristics such as gender, age, and ethnic origin, on the one hand, and nondiscriminatory transnational access to the social security systems of the member states, on the other. Increased heterogeneity among European varieties of capitalism perpetuates the different ranges and speeds of these integration dimensions. We conclude that the Polanyi-in-Brussels hypothesis is misleading. Politically enforced social integration has not made much progress in the last decades, while market-enforcing integration and European nondiscrimination policies have asymmetrically profited from “integration through law.” So far, the impact of European integration on political economy has been “Hayekian” rather than “Polanyian.” Jüngst haben Caporaso und Tarrow argumentiert, die Rechtsprechung des Europäischen Gerichtshofs (EuGH) weise zunehmend soziale Züge auf und führe dazu, dass die europäische Integration eine „Polanyische“ Richtung einnehme. Wir wenden uns gegen diese These und unterscheiden drei Dimensionen der europäischen Wirtschafts- und Sozialintegration: die marktkorrigierende Integration, die marktschaffende Integration und die Schaffung eines europäischen Antidiskriminierungsraums, wobei letztere aus zwei Subdimensionen besteht, nämlich der Nichtdiskriminierung aus Gründen wie denen des Alters, der ethnischen Zugehörigkeit und des Geschlechts einerseits, und der Durchsetzung eines diskriminierungsfreien transnationalen Zugangs zu den sozialen Sicherungssystemen der Mitgliedstaaten andererseits. Die gestiegene Heterogenität europäischer Spielarten des Kapitalismus perpetuiert die unterschiedlichen Reichweiten und Geschwindigkeiten der Integration in den drei Dimensionen. Wir kommen zu dem Ergebnis, dass die „Polanyi in Brüssel“-These unzutreffend ist. Während die politisch herbeigeführte, soziale Integration kaum Fortschritte macht, profitieren die marktschaffende Integration und die europäische Antidiskriminierungspolitik von der „Integration durch Recht“. Die europäische Integration trägt daher weit mehr „Hayeksche“ als „Polanyische“ Züge.
Keywords: Europe; Polanyi-in-Brussels hypothesis